A Study of the Efficiency of Solar Paddy Dryer Conveyor System - Inyasr, Chaleedol; Rakkanrane, Pongphol; Sagulpongmalee, Kangsadan; Prattanarak, Chermthong; Intanin, Jutiporn; Khangsantia, Suparat (Thai Industrial Engineering Network Journal, 2023)
The objective of this research is to study of the efficiency of solar paddy dryer conveyor system. It has designed a solar dryer structure made of steel, walls and roof with polycarbonate sheets. It has a continuous vortex moving conveying system into the paddy drying room using a 3-meter shaftless screw conveyor. There is an electric brushless DC motor with 750 watts 48 volts, which is powered by lithium batteries with 53 volts 30 amp-hours (Ah). The experiment of the drying system was conducted during 6:00-18:00 hr. The results showed that the average temperature inside the drying chamber was 41.44 °C. The thermal efficiency compared to the day’s average solar radiation efficiency was 18.88%. In addition, 50 kg of paddy was dried by solar energy with an initial moisture content of 19% to a final moisture content of 14%. The speed adjustment of the shaftless screw conveyor paddy rice conveying system was tested at 3 levels: 65, 144 and 155 rpm which found that the percentage of broken paddy was 13.63%, 19.04% and 22.22% respectively. The results of this study suggest that the speed of conveying paddy into the drying room at 65 rpm had the least effect on the percentage of paddy fragmentation, with the increase of the speed of the paddy on the increase of the percentage of fragmentation of paddy.